Cover Picture: New Hexanuclear Niobium Cluster Compounds with Perfluorinated Ligands Made Using Ionic Liquids (Z. Anorg. Allg. Chem. 4/2017). Issue 4 (February 2017) - Weiß, Daniel Holger; Schröder, Florian; Köckerling, Martin
Abstract : The cover picture shows the versatile cation environment of the [Nb6 Cl12 (TFA)6 ] 4– cluster anion (TFA: trifluoroacetate), which forms in the ionic liquid (TMG‐H)TFA (TMG‐H + : tetramethylguanidinium). After a short reaction time crystals of (TMG‐H)4 [Nb6 Cl12 (TFA)6 ] form (Level 1). Within the IL a slow chemical reactions happens between the TMG‐H + cations and the TFA – anions, leading to the formation of TMGTFAA‐H + cations (TMGTFAA‐H + : tetramethylguanidinium‐trifluoroacetamide). After 2 days of reaction time crystals consisting of the same cluster anion and both, TMG‐H + and TMGTFAA + cations form (Level 2). Finally, after 7 days, crystals of the cluster anion with TMGTFAA‐H + cations only are obtained (Level 3). More details can be found in the article by Daniel H. Weiß, Florian Schröder and Martin Köckerling on pages 345.